A comparative study of the serum levels of antiphospholipid antibodies in hypertensive disorder of pregnancy and normotensive pregnancy - Kaur, Guljit; Pahwa, Sangeeta; Kaur, Amanbeer; Nagpal, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Antiphospholipid antibodies have been associated with a number of obstetric complications however their role in the pathogenesis of preeclampsia has remained uncertain Therefore, the utility of screening for antiphospholipid antibodies among women at risk for recurrent hypertensive disorder of pregnancy is still doubtful. This study is aimed to clarify relationship between hypertensive pregnancies and APLA. Methods: A prospective, randomized was conducted and, 120 patients after 20 weeks of gestation were studied. 60 patients had hypertensive disorder in pregnancy and 60 were normotensive. Blood samples were obtained from them under all asepsis, serum was separated and tested for Antiphospholipid antibodies (Anticardiolipin, anti beta 2 glycoprotein I, phosphatidyl -serine, -inositol, -ethanolamin, -choline and sphingomyelin and lupus anticoagulant), apart from other routine investigations using Aeskulsia Phospholipid-Screen-GM. Results: 4/60 and 3/60 hypertensive patients had raised IgM and IgG levels respectively. Their values came in equivocal range. 2 of the normotensive patients had equivocal range values of both IgM/IgG. Mean of IgM APLA in hypertensive and normotensive patients was 2.54 and 1.67 respectively and difference between these values was statistically non significant (p=0.081). Mean of APTT is similarly statistically non significant in two groups (p=0.817). Conclusions: No significant correlation between the hypertensive state in pregnancy and antiphospholipid antibodies, hence this test should not be recommended as a screening test in pregnancies and there was no need to assess these antibodies in the hypertensive cases of pregnancy without the history of thrombosis or autoimmune diseases.